Agricultural corridors as ‘demonstration fields’: infrastructure, fairs and associations along the Beira and Nacala corridors of Mozambique - Gonçalves, Euclides (Journal of Eastern African Studies, 2020)
In the past decade, the Mozambican government has been mobilizing international capital to build and renovate transport infrastructure in the central and northern areas of the country, with the aim of creating agricultural corridors. Based on ﬁeld research conducted in two districts along the Beira and Nacala corridors, I examine those occasions when international capital and national agricultural policy meet smallholders in the implementation of agricultural projects. This article oﬀers a performative analysis of the constitution of agricultural corridors. I argue that agricultural corridors emerge on those occasions when international funders and investors, national elites, local bureaucrats and smallholders overstate the success of agricultural projects and constitute what I have termed ‘demonstration ﬁelds’. Regardless of the implementation of blueprints, agricultural corridors gain spatial and temporal materiality from the performance of presenting agricultural projects as successful, such as at the unveiling of agro-related infrastructure, at agricultural fairs and on occasions involving smallholders’ associations.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Beira; GP - Nampula; GP - Sofala; L - english / inglês; M - ethnography / etnografia; agriculture / agricultura; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura

Juventude urbana e redes sociais em Moçambique: a participação política dos conectados desamparados - Tsandzana, Dércio (Comunicação e Sociedade, 2018)
Nos últimos 10 anos, os estudos sobre a participação política por intermédio das redes sociais marcam o debate na área dos estudos dos média. Em Moçambique, de forma particular, e no mundo, de forma geral, a juventude representa o centro galvanizador que encontra no uso das redes socias uma ferramenta quase ideal de expressão sobre as suas frustrações decorrentes da sua situação de gritante miséria social – desemprego e incerteza de vida constante a que os jovens se encontram expostos. Com o presente artigo, pretendemos analisar o papel das redes sociais, concretamente o Facebook, no engajamento político e social da juventude urbana em Moçambique, considerando um horizonte que abarca os últimos quatro anos, 2014-2017. Como resultado, concluímos que embora a sua expansão nos últimos anos, as redes sociais ainda não podem ser consideradas, no seu todo, como espaços que permitam uma efectiva participação política da juventude, decorrente do facto de a internet ser menos abrangente, por um lado, e do fraco interesse da juventude em questões políticas em Moçambique, por outro. EN: In the last 10 years, studies on political participation through social networks have marked the debate in the field of media studies. In Mozambique, particularly, and in the world, in general, youth represent the galvanizing centre that finds in the use of social networks an almost ideal tool of expression about their frustrations due to their situation of blatant social misery – unemployment and constant life uncertainty to which youth are exposed. With this article, we intend to analyse the role of social networks, specifically Facebook, in the political and social engagement of urban youth in Mozambique, considering a timeline that covers the last four years, 2014 to 2017. As a result, it is concluded that, despite the expansion of social networks in recent years, they cannot yet be considered as spaces for effective political participation by youth, due to the fact that the internet is less comprehensive, on the one hand, and the weak youth interest in political issues in Mozambique, on the other.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - central / centro; G - south / sul; GD - Beira; GP - Maputo; GP - Sofala; L - portuguese / português; citizenship & participation / cidadania e participação; decentralization / descentralização; youth / juventude

Artisanal gold mining and rural development policies in Mozambique: Perspectives for the future - Dondeyne, Stefaan; Ndunguru, Eduardo (Futures, 2014)
Despite Mozambique's great natural resource wealth and strong economic growth, rural poverty remains high countrywide. The challenge is thus finding ways to turn this wealth into development opportunities. For many rural people in central Mozambique, artisanal gold mining is the most direct source of income and this is most likely to remain so. Drawing on our personal experiences, we reflect on the future of artisanal gold mining in Mozambique. The government's strategy consists of promoting improved technologies and encouraging artisanal miners to establish themselves as businesses by creating miners associations. This has proved successful where the ore allows for sufficiently long exploitation, in practice, where reef gold occurs. The same cannot be said, however, of colluvial or alluvial deposits, where placer gold is mined. Given the variable nature of these deposits, accompanying mining activities are relatively short-lived at such sites. In these cases, local authorities and community representatives must play an expanded role in enforcing good mining practices. Doing so would be in line with the country's current decentralisation and democratisation policies in relation to rural development.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - central / centro; GP - Sofala; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais; rural development / desenvolvimento rural

‘Operation of the Market's Study. How the poor access, hold and trade land: Findings from research in two settlements in Tete, Mozambique - Gordon, Ross; Taljaard, Reathe; Massuanganhe, Egildo, Egildo (Progressus Research Development Consultancy, 2013)
The way in which informal land transactions occur and the extent to which they result in tenure security and asset creation in these informal settlements is not well understood. For this reason this study comprises research into two informal settlements (namely Matundo and Mateus Sansão Muthemba [Sansão Muthemba]) in Tete, Mozambique, so as to understand how the poor access, hold and trade land. This research forms part of a larger research programme being undertaken by Urban LandMark which includes similar studies in Lilongwe (Malawi), Maputo (Mozambique), Luanda (Angola) and Durban, Cape Town and Johannesburg (South Africa). Reports on these other research projects can be seen on www.urbanlandmark.co.za.
Keywords: DUAT (Direito do uso e aproveitamento da terra) / Land Use and Benefit Right; G - Mozambique / Moçambique; G - central / centro; GP - Tete; L - english / inglês; governance / governação; land governance / gestão de terra

Juventude(s) e AIDS em Moçambique: Um Estudo Qualitativo no Distrito de Nhamatanda - Chicamisse, Francisco Armindo Zinhame (Universidade Federal de São Paulo, 2013)
O presente estudo pretende compreender como são desenvolvidas as ações de prevenção do HIV do Programa Geração Biz (PGB) direcionadas aos jovens dos 15-24 anos e, dessa forma buscar a compreensão da possível vulnerabilidade destes a infecção pelo HIV no distrito de Nhamatanda em Moçambique. Para o alcance deste desiderato baseei-me numa abordagem qualitativa, embasada no método etnográfico. No processo de coleta de dados privilegiei a observação participante, complementada por entrevistas semi-estruturadas e uma extensiva pesquisa bibliográfica. No distrito de Nhamatanda os jovens dos 15-24 anos constituem um dos segmentos populacionais mais afetados pelo HIV/AIDS, com uma taxa de prevalência estimada em 30,5% no ano de 2007, sendo por isso considerado um dos grupos mais vulneráveis a infecção pelo HIV. As ações de prevenção do HIV voltadas para este grupo são desenvolvidas pelo PGB, através das suas três componentes: escolar, comunitária e clínica. Entretanto, estas ações ainda estão assentadas na premissa de que a simples transmissão de informação implica na mudança de comportamentos dos jovens. Ademais, as ações de prevenção acabam tendo por vezes um caráter setorial e descontínuo, o que não permite o alcance de resultados mais duradouros no âmbito da prevenção do HIV. Os resultados deste estudo sugerem que as ações de prevenção do HIV ainda não se têm traduzido na redução considerável da referida vulnerabilidade dos jovens (15-24) a infecção pelo HIV neste distrito. Estas ações colocam por vezes os jovens em situações de maior suscetibilidade a infecção pelo HIV. Portanto, há uma necessidade de se repensar no modo como estas ações têm sido operacionalizadas, reelaborar os modelos pedagógicos que as norteiam e adequar os conteúdos semânticos das mensagens em função dos diferentes contextos socioculturais em que a epidemia se espraia.
Keywords: G - Mozambique / Moçambique; G - central / centro; GD - Nhamatanda; GP - Sofala; Health PEA; L - portuguese / português; access to services / acesso a serviços; health / saúde; youth / juventude

‘Opitanha’ Revisited Assessing the Implications of PARPA II in Rural Northern Mozambique 2006-2009 - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2010)
This report is part of the efforts to monitor and evaluate the implications of Mozambique’s Poverty Reduction Strategy PARPA II (GdM 2005). Three qualitative and participatory studies have already been carried out in three different areas of the country: One in the District of Murrupula in Nampula Province (Tvedten, Paulo & Rosário 2006); one in four bairros in the capital Maputo (Paulo, Rosário & Tvedten 2007); and one in the district of Buzi in Sofala Province (Rosário, Tvedten & Paulo 2008). Each of these studies is to be followed up in order to ascertain changes in social relations and cultural perceptions of poverty and well-being, by visiting the same local administrations, the same communities and the same households after a period of three years. This report is the first in the series of the three such follow-up studies, with the Maputo and the Buzi studies planned for 2010 and 2011, respectively.
Keywords: *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Maputo; GP - Nampula; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização

"Opitanha:" Social Relations of Rural Poverty in Northern Mozambique - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2006)
Research-based information is recognised as crucial for Mozambique's endeavours to reduce its poverty. This first report in a series of three qualitative studies on poverty in Mozambique focuses on the district of Murrupula in Nampula province. In Chapter 1 we argue that qualitative studies are important for the monitoring and evaluation of poverty reduction policies. They inform quantitative data and correlations by testing causal hypotheses on the ground. They discover processes and interdependencies related to non-tangible dimensions of poverty such as vulnerability and powerlessness. They test and reassess central concepts and units of poverty analysis. Finally, they involve the poor themselves in the analysis of their own situation in ways that are difficult with formal questionnaire surveys. In Chapter 2 we present central quantitative expressions of poverty in Mozambique as points of reference. We start by outlining some of the broad development trends, including urbanisation, feminisation of poverty and HIV/AIDS, and then analyse data on Mozambique and Nampula to highlight similarities and differences. Chapter 3 provides a background profile of the area under study, predicated on the assumption that the political, economic and sociocultural context is important for understanding social relations of poverty. A brief history emphasising how Murrupula was constrained in its development through the late colonial era, the Frelimo socialist experiment and the war leads into an outline of the responsibilities of the District Administration, the role of traditional authorities, and the overall social and economic situation in the district. Chapter 4 is built around the survey undertaken for this study, and outlines socioeconomic conditions and determinants of poverty with a focus on employment and income, education and health. It also looks at the implications of geographical space, especially distance from the main economic and population centres, for poverty and poverty alleviation. Chapter 5 focuses on the issue of social relations of poverty, and processes of impoverishment, marginalisation and social exclusion. Its point of departure is people's own emic perceptions of poverty, examining relationships between different categories of the poor within the household and the extended family, traditional institutions and the state. Chapter 6 concludes, drawing some preliminary policy implications and outlining the planned follow-up of the current study in urban Maputo and coastal Sofala respectively.Research-based information is recognised as crucial for Mozambique's endeavours to reduce its poverty. This first report in a ser...
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Nampula; L - english / inglês; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização

Mozambique | Tropical Cyclone Eloise Response Situation Report #1 | 25 January - 12 February 2021 - Mozambique
English Situation Report on Mozambique about Camp Coordination and Camp Management, Health, Epidemic, Flood and more; published on 12 Feb 2021 by IOM
Keywords: *tagged; G - Mozambique / Moçambique; G - central / centro; GP - Sofala; L - english / inglês; natural disasters / desastres naturais